The Influence of Body Mass Index on Characteristics of Falls in the Malaysian Elders Longitudinal Research Study. Issue 2 (April 2020) - Kioh, Sheng Hui; Mat, Sumaiyah; Myint, Phyo Kyaw; Ai-Vyrn, Chin; Kamaruzzaman, Shahrul Bahyah; Hairi, Noran N.; Cumming, Robert; Tan, Maw Pin
Abstract : Aim: To compare and contrast falls characteristics between older adults with body mass index of 25.0 kg/m 2 or greater and less than 25.0 kg/m 2 and to further identify potential underlying mechanisms if differences existed. Subjects and Methods: This was a cross-sectional study using data from fallers identified during the first wave of the Malaysian Elders Longitudinal Research study. Basic demographics, falls characteristics, fear of falling, medical comorbidities, and lifestyle factors were obtained during a home-based computer-assisted interview, while anthropometric measurements, body composition, and physical performance were collected during the hospital-based health check. Results: Of the 302 individuals with 1 or more falls in the previous 12 months, mean age (SD) = 69.6 (7.7) years, 152 individuals (50.3%) were in the body mass index of 25.0 group or greater. Fallers with body mass index of 25.0 or greater were more likely to have fallen in the bedroom and on the stairs (adjusted odds ratio = 2.50; 95% confidence interval, 1.10-5.73) and less likely to fall in the afternoon (adjusted odds ratio = 0.47; 95% confidence interval, 0.26-0.83) after adjustment for potential confounders. Conclusions: Our study suggests that mechanisms of falls may differ in those with excess body weight, who may benefit from specific targeted fall prevention programmes.